2015
DOI: 10.2298/psi1502149s
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical peer interaction as a factor of formal operations development in more competent students

Abstract: This paper deals with the role of asymmetrical peer interaction in the development of formal operational thinking. The relevance of the research lies in the fact that influence of peers? interaction is rarely examined in the context of the development of formal operations and in the fact that effects of asymmetrical interaction are more investigated regarding the less competent participants. The results show no influence of the interaction on the development of formal operations in more compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…The results showed that LC students progressed, and that interaction did not affect MC students (Stepanović Ilić, 2015). However, it transpired that MC students were a very heterogeneous group regarding their performance on the post-test (Stepanović Ilić, 2015).…”
Section: Problemmentioning
confidence: 92%
See 3 more Smart Citations
“…The results showed that LC students progressed, and that interaction did not affect MC students (Stepanović Ilić, 2015). However, it transpired that MC students were a very heterogeneous group regarding their performance on the post-test (Stepanović Ilić, 2015).…”
Section: Problemmentioning
confidence: 92%
“…The results showed that LC students progressed, and that interaction did not affect MC students (Stepanović Ilić, 2015). However, it transpired that MC students were a very heterogeneous group regarding their performance on the post-test (Stepanović Ilić, 2015). Hence this study focuses on those who progressed or regressed the most, assuming that the explanation for different interaction outcomes could be related to the nature of peer dialogue.…”
Section: Problemmentioning
confidence: 97%
See 2 more Smart Citations
“…разумевање потреба и намера друге особе, јесте битна компонента у развоју комплексног формално-операционалног мишљења. кооперација међу вршњацима доприноси развоју логичког мишљења будући да својим својствима подстиче развој рефлексије и регулације сопствених мисаоних процеса (Stepanović, 2010;Stepanović Ilić, 2015).…”
Section: закључакunclassified